Iron-based superconducting composite material and preparation method thereof

By adopting a multi-core composite structure and a silver-tin alloy layer generation method in the iron-based superconducting wire, the problems of mechanical strength and core wire uniformity of the iron-based superconducting wire are solved, and a combination of high mechanical strength and high current carrying performance is achieved.

CN119786146AActive Publication Date: 2025-04-08INST OF ELECTRICAL ENG CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510006049.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-08
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

Iron-based superconducting wires are restricted by the cover material in terms of mechanical characteristics. The tensile strength of the silver cover material is low and difficult to adapt to the needs of strong magnetic field applications. The use of high-strength metal cover material will affect the processing process and core wire uniformity.

Method used

By filling the single mandrel in the silver-clad sleeve and filling the tin wire between the single mandrel and the silver-clad sleeve, a multi-core composite ingot is formed, followed by cyclic surface reduction processing and intermittent annealing treatment to generate a silver-tin alloy layer, and finally heat treatment is carried out to generate an iron-based superconducting material.

Benefits of technology

Without reducing the current carrying performance, the mechanical strength and uniformity of the iron-based superconducting composite material are significantly improved, ensuring high tensile strength and high critical current density of the superconducting wire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786146A_ABST
    Figure CN119786146A_ABST
Patent Text Reader

Abstract

The invention provides an iron-based superconducting composite material and a preparation method thereof, and belongs to the field of superconducting materials. The invention provides a preparation method of an iron-based superconducting composite material, which comprises the following steps: filling a silver sheath with a plurality of single-core rods, and then filling gaps between the single-core rods and the silver sheath with tin wires to obtain a multi-core composite ingot; the single-core rod comprises a silver tube and an iron-based superconducting material preparation raw material in the silver tube; the multi-core composite ingot is subjected to cyclic surface reduction machining and intermittent annealing treatment, a silver-tin alloy layer is gradually generated, and a composite ingot containing silver-tin alloy is obtained; the total number of times of annealing treatment in the intermittent annealing treatment is greater than or equal to 2; and performing heat treatment on the composite ingot containing the silver-tin alloy to generate the iron-based superconducting material, thereby obtaining the iron-based superconducting composite material. Intermittent annealing treatment enables interface diffusion to occur between metal sheath silver and the tin wire, silver-tin alloy with high tensile strength is gradually generated, and the tensile strength of the superconducting wire is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of superconducting materials, and in particular to an iron-based superconducting composite material and a preparation method thereof. Background Art

[0002] Iron-based superconducting materials have the advantages of high upper critical field, large critical current and small anisotropy, and are considered to be a new type of high-temperature superconducting material with great application potential in the field of medium-temperature strong magnetic field. Compared with niobium-based low-temperature superconducting materials, iron-based superconductors have high critical transition temperature and critical magnetic field; compared with copper oxide high-temperature superconducting materials, iron-based superconductors have lower material and preparation costs.

[0003] The critical current density of iron-based superconducting wires has reached a practical level, but the improvement of mechanical properties is restricted by the sheath material: silver as a sheath material has low tensile strength and cannot meet the requirements of its strong magnetic field application. If high-strength metals (such as monel, stainless steel) and silver are used as a composite material, it will affect the plastic deformation process of the composite during processing, making it difficult to process and easily causing uneven core wires. How to improve the mechanical strength of the wire while ensuring that the current-carrying performance is not reduced is the key and difficulty in promoting the practical application of iron-based superconducting wires. Summary of the invention

[0004] The invention provides an iron-based superconducting composite material and a preparation method thereof. The iron-based superconducting composite material prepared by the invention has improved mechanical strength and uniform core filament distribution without reducing current carrying performance.

[0005] The present invention provides a method for preparing an iron-based superconducting composite material, comprising the following steps:

[0006] A plurality of single core rods are filled in a silver sheath, and then tin wire is filled in the gap between the single core rods and the silver sheath to obtain a multi-core composite ingot; the single core rod comprises a silver tube and a raw material for preparing an iron-based superconducting material in the silver tube;

[0007] The multi-core composite ingot is subjected to cyclic surface reduction processing and intermittent annealing treatment to gradually generate a silver-tin alloy layer, thereby obtaining a composite ingot containing a silver-tin alloy; the total number of annealing treatments in the intermittent annealing treatment is ≥2;

[0008] The composite ingot containing the silver-tin alloy is subjected to heat treatment to generate an iron-based superconducting material, thereby obtaining the iron-based superconducting composite material.

[0009] Preferably, the chemical formula of the iron-based superconducting material is Ba 1-x K x Fe 2 As 2 , x=0.2~0.5.

[0010] Preferably, the method for preparing the single core rod comprises the following steps:

[0011] The raw materials for preparing the iron-based superconducting material are mixed and filled into the silver tube, and then rotary forging and drawing are performed.

[0012] Preferably, the diameter of the single core rod is 1 / 6 to 1 / 3 of the inner diameter of the silver sheath.

[0013] Preferably, the diameter of the tin wire is 1 / 37 to 1 / 18 of the inner diameter of the silver sheath.

[0014] Preferably, the total number of annealing treatments is 3 times;

[0015] The temperature of each annealing treatment is independently 200 to 300° C., and the time is independently 30 to 120 minutes.

[0016] Preferably, each annealing treatment is performed between two adjacent surface reduction processes;

[0017] The composite ingot containing the silver-tin alloy is annealed when the surface reduction rate is between 30% and 60%.

[0018] Preferably, the surface reduction process includes rotary forging and drawing.

[0019] Preferably, the heat treatment temperature is 600-800°C and the time is 0.5-2h;

[0020] The heat treatment is carried out in a protective atmosphere.

[0021] The present invention also provides an iron-based superconducting composite material prepared by the preparation method described in the above technical solution.

[0022] The addition of low-melting-point tin wire can provide a wetting liquid phase during annealing, thereby effectively removing the gaps between the core wires, thereby improving the cooperative deformation ability of each core wire in the subsequent processing process, and helping to obtain a core wire structure with uniform deformation. In addition, during the intermittent annealing process, the metal sheath silver and the tin wire undergo interfacial diffusion, gradually generating a silver-tin alloy with high tensile strength, which not only ensures that the sheath material maintains good plasticity of silver during the processing, but also significantly improves the tensile strength of the final superconducting wire; by generating a high-strength silver-tin alloy layer during the processing process, the pure silver-superconducting core structure can be preserved, thereby fundamentally ensuring the extremely high current-carrying performance of the superconducting core wire. Therefore, the iron-based superconducting composite material prepared by the present invention not only has a higher critical current density, but also its tensile strength and core wire uniformity can be significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the structure of the composite ingot in the embodiment. DETAILED DESCRIPTION

[0024] The present invention provides a method for preparing an iron-based superconducting composite material, comprising the following steps:

[0025] A plurality of single core rods are filled in a silver sheath, and then tin wire is filled in the gap between the single core rods and the silver sheath to obtain a multi-core composite ingot; the single core rod comprises a silver tube and a raw material for preparing an iron-based superconducting material in the silver tube;

[0026] The multi-core composite ingot is subjected to cyclic surface reduction processing and intermittent annealing treatment to gradually generate a silver-tin alloy layer, thereby obtaining a composite ingot containing a silver-tin alloy; the total number of annealing treatments in the intermittent annealing treatment is ≥2;

[0027] The composite ingot containing the silver-tin alloy is subjected to heat treatment to generate an iron-based superconducting material, thereby obtaining the iron-based superconducting composite material.

[0028] The invention fills a plurality of single core rods in a silver sheath, and then fills tin wires in the gaps between the single core rods and the silver sheath to obtain a multi-core composite ingot.

[0029] In the present invention, the single core rod comprises a silver tube and a raw material for preparing an iron-based superconducting material in the silver tube.

[0030] In the present invention, the volume of the raw material for preparing the iron-based superconducting material is preferably 20% of the volume inside the silver tube.

[0031] In the present invention, the chemical formula of the iron-based superconducting material is preferably Ba 1-x K x Fe 2 As 2 , x=0.2-0.5. In a specific embodiment of the present invention, x may be 0.2, 0.3, 0.4 or 0.5.

[0032] In the present invention, the method for preparing the single core rod preferably comprises the following steps:

[0033] The raw materials for preparing the iron-based superconducting material are mixed and filled into the silver tube, and then rotary forging and drawing are performed.

[0034] The preparation raw material is preferably a metal single substance corresponding to the metal element in the iron-based superconducting material.

[0035] In the present invention, the mixing is preferably performed in a protective atmosphere.

[0036] In the present invention, the inner diameter of the silver tube is preferably 8 mm, and the outer diameter is preferably 10 mm.

[0037] In the present invention, the diameter of the single core rod is preferably 1 / 6 to 1 / 3 of the inner diameter of the silver sheath. In a specific embodiment of the present invention, the diameter of the single core rod may be 1 / 6, 1 / 5, 1 / 4 or 1 / 3 of the inner diameter of the silver sheath. The diameter of the tin wire is preferably 1 / 37 to 1 / 18 of the inner diameter of the silver sheath. In a specific embodiment of the present invention, the diameter of the tin wire may be 1 / 37, 1 / 35, 1 / 32, 1 / 30, 1 / 28, 1 / 26, 1 / 24, 1 / 22, 1 / 20 or 1 / 18 of the inner diameter of the silver sheath.

[0038] After obtaining the multi-core composite ingot, the present invention performs cyclic surface reduction processing and intermittent annealing treatment on the multi-core composite ingot to gradually generate a silver-tin alloy layer to obtain a composite ingot containing a silver-tin alloy.

[0039] In the present invention, the surface reduction process preferably includes rotary forging and drawing.

[0040] In the present invention, each annealing treatment during the intermittent annealing treatment is preferably carried out between two adjacent surface reduction processes; the composite ingot containing the silver-tin alloy is preferably annealed when the surface reduction rate is between 30% and 60%, and the total number of annealing treatments is ≥ 2 times. In a specific embodiment of the present invention, the number of annealing treatments can be 3 times. In a specific embodiment of the present invention, the silver tube with an inner diameter of 7 mm is annealed when the surface is reduced to a diameter of 5 mm, 2.5 mm and 1.2 mm, respectively.

[0041] In the present invention, the temperature of each annealing treatment is preferably independently 200-300°C, and the time is preferably 30-120min. In a specific embodiment of the present invention, the temperature of each annealing treatment can be independently 200°C, 220°C, 240°C, 260°C, 280°C or 300°C, and the time can be 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min or 120min.

[0042] After obtaining the composite ingot containing the silver-tin alloy, the present invention heat-treats the composite ingot containing the silver-tin alloy to generate an iron-based superconducting material to obtain the iron-based superconducting composite material

[0043] In the present invention, the temperature of the heat treatment is preferably 600-800°C, and the time is preferably 0.5-2h. In a specific embodiment of the present invention, the temperature of the heat treatment can be 600°C, 650°C, 700°C, 750°C or 800°C, and the time can be 0.5h, 1h, 1.5h or 2h;

[0044] In the present invention, the heat treatment is preferably performed in a protective atmosphere.

[0045] The present invention also provides an iron-based superconducting composite material prepared by the preparation method described in the above technical solution.

[0046] In the present invention, the iron-based superconducting composite material preferably comprises a wire or a tape.

[0047] The iron-based superconducting composite material and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0048] Figure 1 Schematic diagram of the structure of the composite ingot in the embodiment: 1-silver tube, 2-single core rod, 3-tin wire.

[0049] Example 1

[0050] In an Ar protective atmosphere, Ba chips, K blocks, Fe powder, and As powder were mixed according to the chemical formula Ba 0.5 K 0.5 Fe 2 As 2 The molar ratio shown is fully and evenly mixed to obtain Ba122 superconducting precursor powder; 21g Ba122 superconducting precursor powder is loaded into a 12cm long silver tube (tube inner diameter 8mm, outer diameter 10mm), and then the silver composite tube containing the mixed precursor powder is forged to 3.4mm, and then drawn to 2.3mm to obtain a single core rod. The cleaned 7 single core rods with a size of Φ2.3mm are assembled in a silver sheath with a size of Φ10 / Φ7×240mm, and the positions where the edges cannot be filled with complete single core rods are filled with 6 Φ0.1mm tin wires to obtain a composite ingot. The composite ingot is then processed according to the forging-drawing process, and intermediate annealing at 200℃ for 40min is performed at Φ5, Φ2.5 and Φ1.2mm to eliminate processing stress and generate a silver-tin alloy solid solution layer, and finally processed into Φ0.8mm wire. The processed wire is placed in a vacuum annealing furnace, evacuated and filled with high-purity argon, heated to 600°C and kept for 2 hours, and finally cooled to room temperature along with the furnace.

[0051] The critical current and tensile strength of the sample were measured by the standard four-lead method and tensile test, and the transmission critical current density was 1.5×10 5 A / cm 2 (4.2K, 10T), iron-based superconducting wire with a tensile strength of 350MPa.

[0052] Example 2

[0053] In an Ar protective atmosphere, Ba chips, K blocks, Fe powder, and As powder were mixed according to the chemical formula Ba 0.6 K 0.4 Fe 2 As 2The molar ratio shown is fully and evenly mixed to obtain Ba122 superconducting precursor powder; 21g Ba122 superconducting precursor powder is loaded into a 12cm long silver tube (tube inner diameter 8mm, outer diameter 10mm), and then the silver composite tube containing the mixed precursor powder is forged to 3.4mm, and then drawn to 2.3mm to obtain a single core rod. The cleaned 7 single core rods with a size of Φ2.3mm are assembled in a silver sheath with a size of Φ10 / Φ7×240mm, and the positions where the edges cannot be filled with complete single core rods are filled with 6 Φ0.2mm tin wires to obtain a composite ingot. The composite ingot is then processed according to the forging-drawing process, and intermediate annealing at 300℃ for 60min is performed at Φ5, Φ2.5 and Φ1.2mm respectively to eliminate processing stress and generate a silver-tin alloy solid solution layer, and finally processed into Φ0.8mm wire. The processed wire is placed in a vacuum annealing furnace, evacuated and filled with high-purity argon, heated to 800°C and kept for 0.5h, and finally cooled to room temperature along with the furnace.

[0054] The critical current and tensile strength of the sample were measured by the standard four-lead method and tensile test, and the transmission critical current density was 10 5 A / cm 2 (4.2K, 10T), iron-based superconducting wire with a tensile strength of 300MPa.

[0055] Comparative Example 1

[0056] In an Ar protective atmosphere, Ba chips, K blocks, Fe powder, and As powder were mixed according to the chemical formula Ba 0.6 K 0.4 Fe 2 As 2 The molar ratio shown is fully and evenly mixed to obtain Ba122 superconducting precursor powder; 21g Ba122 superconducting precursor powder is loaded into a 12cm long silver tube (tube inner diameter 8mm, outer diameter 10mm), and then the silver composite tube containing the mixed precursor powder is forged to 3.4mm, and then drawn to 2.3mm to obtain a single core rod. The cleaned 7 single core rods with a size of Φ2.3mm are assembled in a silver sheath with a size of Φ10 / Φ7×240mm to obtain a composite ingot. The composite ingot is then processed according to the forging-drawing process, and intermediate annealing at 300℃ for 40min at Φ5, Φ2.5 and Φ1.2mm is performed to eliminate processing stress, and finally processed into Φ0.8mm wire. The processed wire is placed in a vacuum annealing furnace, evacuated and filled with high-purity argon, heated to 800℃ and kept warm for 0.5h, and finally cooled to room temperature with the furnace.

[0057] The critical current and tensile strength of the sample were measured by the standard four-lead method and tensile test, and the transmission critical current density was 10 5 A / cm 2(4.2K, 10T), iron-based superconducting wire with a tensile strength of 75MPa.

[0058] Comparative Example 2

[0059] In an Ar protective atmosphere, Ba chips, K blocks, Fe powder, and As powder were mixed according to the chemical formula Ba 0.5 K 0.5 Fe 2 As 2 The molar ratio shown is fully and evenly mixed to obtain Ba122 superconducting precursor powder; 21g Ba122 superconducting precursor powder is loaded into a 12cm long silver tube (tube inner diameter 8mm, outer diameter 10mm), and then the silver composite tube containing the mixed precursor powder is forged to 3.4mm, and then drawn to 2.3mm to obtain a single core rod. The cleaned 7 single core rods with a size of Φ2.3mm are assembled in a silver sheath with a size of Φ10 / Φ7×240mm, and the positions where the edges cannot be filled with complete single core rods are filled with 6 copper wires with a size of Φ0.1mm to obtain a composite ingot. The composite ingot is then processed according to the forging-drawing process, and intermediate annealing at 200℃ for 40min is performed at Φ5, Φ2.5 and Φ1.2mm to eliminate processing stress, and finally processed into Φ0.8mm wire. The processed wire is placed in a vacuum annealing furnace, evacuated and filled with high-purity argon, heated to 600°C and kept for 2 hours, and finally cooled to room temperature along with the furnace.

[0060] The critical current and tensile strength of the sample were measured by the standard four-lead method and tensile test, and the transmission critical current density was 1.5×10 5 A / cm 2 (4.2K, 10T), iron-based superconducting wire with a tensile strength of 100MPa.

[0061] Comparative Example 3

[0062] In an Ar protective atmosphere, Ba chips, K blocks, Fe powder, and As powder were mixed according to the chemical formula Ba 0.6 K 0.4 Fe 2 As 2After the molar ratio shown is fully and evenly mixed to obtain Ba122 superconducting precursor powder, 5% of the mass of tin powder of Ba122 superconducting precursor powder is added to improve the connectivity of Ba122 superconducting grains to obtain tin-containing Ba122 superconducting precursor powder; 21g of tin-containing Ba122 superconducting precursor powder is loaded into a 12cm long silver tube (tube inner diameter 8mm, outer diameter 10mm), and then the silver composite tube containing the mixed precursor powder is swaged to 3.4mm, and then pulled to 2.3mm to obtain a single core rod. The cleaned 7 single core rods of size Φ2.3mm are assembled in a silver sheath of size Φ10 / Φ7×240mm to obtain a composite ingot. The composite ingot is then processed according to the swaging-drawing process, and intermediate annealing at 300℃ for 40min is performed at Φ5, Φ2.5 and Φ1.2mm to eliminate processing stress, and finally processed into Φ0.8mm wire. The processed wire is placed in a vacuum annealing furnace, evacuated and filled with high-purity argon, heated to 800°C and kept for 0.5h, and finally cooled to room temperature along with the furnace.

[0063] The critical current and tensile strength of the sample were measured by the standard four-lead method and tensile test, and the transmission critical current density was 10 5 A / cm 2 (4.2K, 10T), iron-based superconducting wire with a tensile strength of 75MPa.

[0064] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an iron-based superconducting composite material, characterized in that: The following steps are involved: A plurality of single core rods are filled in a silver sheath, and then tin wire is filled in the gap between the single core rods and the silver sheath to obtain a multi-core composite ingot; the single core rod comprises a silver tube and a raw material for preparing an iron-based superconducting material in the silver tube; The multi-core composite ingot is subjected to cyclic surface reduction processing and intermittent annealing treatment to gradually generate a silver-tin alloy layer, thereby obtaining a composite ingot containing a silver-tin alloy; the total number of annealing treatments in the intermittent annealing treatment is ≥2; The composite ingot containing the silver-tin alloy is subjected to heat treatment to generate an iron-based superconducting material, thereby obtaining the iron-based superconducting composite material.

2. The preparation method according to claim 1, characterized in that: The chemical formula of the iron-based superconducting material is Ba 1- x K x Fe2As2, x=0.2~0.

5.

3. The preparation method according to claim 1 or 2, characterized in that: The method for preparing the single core rod comprises the following steps: The raw materials for preparing the iron-based superconducting material are mixed and filled into the silver tube, and then rotary forging and drawing are performed.

4. The preparation method according to claim 1, characterized in that: The diameter of the single core rod is 1 / 6 to 1 / 3 of the inner diameter of the silver sheath.

5. The preparation method according to claim 1 or 4, characterized in that: The diameter of the tin wire is 1 / 37 to 1 / 18 of the inner diameter of the silver sleeve.

6. The preparation method according to claim 1, characterized in that: The total number of annealing treatments is 3 times; The temperature of each annealing treatment is independently 200 to 300° C., and the time is independently 30 to 120 minutes.

7. The preparation method according to claim 1 or 6, characterized in that: Each annealing treatment is carried out between two adjacent surface reduction processes; The composite ingot containing the silver-tin alloy is annealed when the surface reduction rate is between 30% and 60%.

8. The preparation method according to claim 1, characterized in that: The surface reduction process includes rotary forging and drawing.

9. The preparation method according to claim 1, characterized in that: The heat treatment temperature is 600-800°C and the time is 0.5-2h; The heat treatment is carried out in a protective atmosphere.

10. The iron-based superconducting composite material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Iron-based compound superconducting wire or tape prepared from silver sheath

    CN101707083A

  • Iron-based superconducting composite wire and preparation method thereof

    CN112489884A

  • Metal coated multicore superconducting wire and its manufacture

    JP1996190818A

  • Superconducting wire material and method for preparation thereof, and superconducting magnet using the same

    US20050174202A1